Research on Integrated Innovation Design Education for Cultivating the Innovative and Entrepreneurial Ability of Industrial Design Professionals - Hu, Weifeng; Hu, Yue; Lyu, Yilin; Chen, Yan (Frontiers in Psychology, 2021)
In the industrial design industry, innovation and entrepreneurship made by professional and technical talents will become an important trend in the future development of economy and society. The great changes in the design industry, the diversification and complication of design objects, the relatively restricted knowledge structure of design talents, the lack of entrepreneurial experience and other reasons lead to the low success rate of industrial design talents entrepreneurship. The purpose of this research is to analyze and explore the effects of integrated innovative design teaching modes and methods of cultivating innovative and entrepreneurial abilities of industrial design professionals, and help industrial design professionals to improve their success rate of establishing new companies. This research also aims to improve the innovative and entrepreneurial ability of industrial design professionals in the integrated innovation and design teaching reform by integrating the theories and methods of industrial design professional training links such as the objectives, teaching contents, teaching modes and methods, performance evaluation of innovation and design education, and combining with the requirements of innovative and entrepreneurial ability training of industrial design professionals. In this research the educational reform of integrated innovation design in a certain Chinese university is taken as an example to carry out theoretical research and practical application. The results of this research show that the theory and method of integrated innovation design education has made significant contributions to the enhancement of innovative and entrepreneurial ability of industrial design professionals. This research also reveals a feasible direction for constructing an industrial design innovative and entrepreneurial talent training system that adapts to the transformation and upgrading of the design industry. Meanwhile, methods and teaching modes applied in this research can be promoted in relevant or similar majors to make innovation and entrepreneurship education in colleges and universities more professional, stimulate students’ entrepreneurial consciousness and improve students' abilities of innovation and entrepreneurship.